Pengaruh Self-Confidence Terhadap Kemampuan Pemecahan Masalah Matematis (KPMM) Siswa SMP - Lathifah, Nida Nabilah; Indah Puspita Sari (MUST: Journal of Mathematics Education, Science and Technology, 2024)
The purpose of this study was to determine the effect of students' self-confidence on the mathematical problem solving ability (KPMM) of junior high school students. In this study, the population was all seventh grade students at SMP Negeri 16 Cimahi even semester in the 2023/2024 school year distributed in five classes, namely VIIA to VIIE. In this study, the sample used was class VIIB students, because it was selected using purposive sampling technique as many as 35 students. Quantitative approach and causal comparative design were used in this study, so that the data that have been taken in this study are quantitative data that have been obtained from self-confidence questionnaires and KPMM tests of junior high school students. After the normality test and linearity test were carried out, hypothesis testing was carried out using simple linear regression analysis and a simple linear regression equation was obtained, namely . This means that the greater the students' self-confidence, the positive impact on students' CAR. Based on the results of the coefficient of determination, the conclusion that can be drawn is that self-confidence affects students' KPMM with a large influence of 37.2%.